2003
DOI: 10.2337/diabetes.52.7.1655
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Adiponectin, a Fat-Derived Antidiabetic and Antiatherogenic Factor, by Nuclear Receptors

Abstract: Adiponectin is a fat-derived hormone with antidiabetic and antiatherogenic properties. Hypoadiponectinemia seen in obesity is associated with insulin-resistant diabetes and atherosclerosis. Thiazolidinediones, peroxisome proliferator-activated receptor-␥ (PPAR-␥) agonists, have been shown to increase plasma adiponectin levels by the transcriptional induction in adipose tissues. However, the precise mechanism of such action is unknown. In this study, we have identified a functional PPAR-responsive element (PPRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
505
3
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 670 publications
(540 citation statements)
references
References 55 publications
21
505
3
11
Order By: Relevance
“…However, Maeda et al demonstrated that TZD treatment induces the adiponectin promoter activity by five to 10-fold, suggesting that the induction of adiponectin expression is a consequence of a direct activation of the adiponectin promoter. This work was further confirmed and extended by Iwaki et al, 45 who revealed the existence of a PPRE in the human adiponectin gene. Finally, patients with dominant-negative PPARg mutations responsible for severe insulin resistance and type 2 diabetes have significantly decreased adiponectin levels, again implying that adiponectin is a molecular target of PPARg action.…”
Section: Adiponectin: Physiological Effectssupporting
confidence: 81%
“…However, Maeda et al demonstrated that TZD treatment induces the adiponectin promoter activity by five to 10-fold, suggesting that the induction of adiponectin expression is a consequence of a direct activation of the adiponectin promoter. This work was further confirmed and extended by Iwaki et al, 45 who revealed the existence of a PPRE in the human adiponectin gene. Finally, patients with dominant-negative PPARg mutations responsible for severe insulin resistance and type 2 diabetes have significantly decreased adiponectin levels, again implying that adiponectin is a molecular target of PPARg action.…”
Section: Adiponectin: Physiological Effectssupporting
confidence: 81%
“…The induction of adiponectin but not of leptin by EPA/DHA indicates that the mechanisms controlling the expression of genes for these two adipokines are different. As with thiazolidinediones, EPA and DHA may upregulate Adipoq by acting as ligands of peroxisome proliferator-activated receptor-γ, the transcriptional regulator interacting directly with Adipoq promoter [8]. The stimulation of Adipoq may also depend on the activation of AMPK, since AMPK in adipocytes stimulates Adipoq [9] and EPA and DHA activate hepatic AMPK [10].…”
Section: Discussionmentioning
confidence: 99%
“…47 The Ala-allele of the PPARG Pro12Ala polymorphism has been associated with a reduced risk for type 2 diabetes in several populations. 48 The Pro12Ala polymorphism has also been suggested to affect the adiponectin plasma levels, Ala-carriers having lower APM1 expression in a Japanese population.…”
Section: Discussionmentioning
confidence: 99%